Mini-Basketball Training Program Improves Physical Fitness and Social Communication in Preschool Children with Autism Spectrum Disorders - Cai, Ke-Long (J Hum Kinet, 2020)
This investigation examined the effects of a 12-week mini-basketball training program (MBTP) on physical fitness and social communication in preschool children with autism spectrum disorders (ASD). The study applied a quasi-experimental design. Fifty-nine preschool children aged 3-6 years with ASD were assigned to either a MBTP group (n = 30) or a control group (n = 29). Participants in the MBTP group received a scheduled mini-basketball training program (5 sessions per week, forty minutes per session) for twelve consecutive weeks, while the control group was instructed to maintain their daily activities. The physical fitness test and the parent-reported Social Responsiveness Scale Second Edition (SRS-2) test were performed before and after the intervention. Results indicated that the 12-week MBTP facilitated performance in the physical fitness test, particularly in speed-agility and muscular strength abilities. Additionally, children in the MBTP group demonstrated improvement in SRS-2 performance in social awareness, social cognition, social communication, and autistic mannerisms, whereas no such changes were found in the control group. It may be concluded that the 12-week MBTP could improve physical fitness and social communication in preschool children with ASD, and thus the use of physical exercise intervention as a therapeutic tool for preschoolers with ASD is recommended.